Efisiensi Penggunaan Anggaran Publik dalam Meningkatkan Kesejahteraan Sosial - Ahmad Wahyudi Zein; Muhammad Riski; Allya Zahra Putri Nasution (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study uses a qualitative method to examine the efficiency of public budget utilization in improving social welfare. The focus of this research is on how budget management policies are directed toward meeting basic community needs and promoting equitable social justice. In many cases, inefficiencies arise due to poorly targeted planning, overlapping programs, and the lack of proper evaluation of activities funded by national or regional budgets. This study reviews relevant literature and public policy regulations, analyzing policy data in the context of budget efficiency. The findings indicate that social welfare can be significantly enhanced when budget allocations are directed toward priority programs supported by consistent evaluation mechanisms. A synergistic effort between policymakers and program implementers is essential to ensure that public spending effectively achieves social development goals. This research also highlights the importance of a result-based approach in fiscal management to ensure that every dollar spent delivers tangible benefits to society.